An Evaluation of Qualitative Criteria of Subway Station According to Audience-Based Criticism - mohsen kameli (تحقیقات کاربردی علوم جغرافیایی)
Inland traffic has become a growing phenomenon for today's civilized society, which in addition to the movement of passengers, the desirable feature of the stations should be used. Due to the high volume of users of the subway and the long-term stops of passengers, stations have become an effective venue for urban daily activities. Considering the growing trend of metro expansion in Tehran metropolis and the increasing need for it, special attention is paid to the quality of the environment of stations The metro should be considered as a metropolitan environment for the social interactions of citizens. The purpose of this paper is to investigate and evaluate physical, functional and psychological criteria in the design of metro stations and the effect of these components on the quality of stations from the viewpoint of metro users and also provide a solution to improve the quality of space stations. The research method is descriptive-analytic research based on the survey and interview technique, questionnaire, and observation were used. The data obtained from the field method are quantitative and qualitative data. Qualitative data is the result of observation in the place or photographs and quantitative data obtained from the questionnaire and analyzed by SPSS software.